The Essential Role of Type I Interferons in Differentiation and Activation of Tumor-Associated Neutrophils - Pylaeva, Ekaterina; Lang, Stephan; Jablonska, Jadwiga (Frontiers in Immunology, 2016)
Type I interferons (IFNs) were first characterized in the process of viral interference. However, since then interferons are found to be involved in a wide range of biological processes. In the mouse, type I IFNs comprise a large family of cytokines. At least 12 IFN-alphaand one IFN-betacan be found and they all signal through the same receptor (IFNAR). A hierarchy of expression has been established for type I IFNs, where IFN-beta is induced first and it activates in a paracrine and autocrine fashion a cascade of other type I IFNs. Besides its importance in the induction of the IFN cascade, IFN-beta is also constitutively expressed in low amounts under normal non-inflammatory conditions thus facilitating “primed” state of the immune system. In the context of cancer, type I IFNs show strong anti-tumor function as they play a key role in mounting anti-tumor immune responses through the modulation of neutrophil differentiation, activation and migration. Owing to their plasticity, neutrophils play diverse roles during cancer development and metastasis since they possess both tumor promoting (N2) and tumor limiting (N1) properties. Notably, the differentiation into anti-tumor phenotype is strongly supported by type I IFNs. It could also be shown that these cytokines are critical for the suppression of neutrophil migration into tumor and metastasis site by regulating chemokine receptors e.g. CXCR2 on these cells and by influencing their longevity. Type I IFNs limit the life span of neutrophils by influencing both, the extrinsic as well as the intrinsic apoptosis pathways. Such anti-tumor neutrophils efficiently suppress the pro-angiogenic factors expression e.g. VEGF and MMP-9. This in turn restricts tumor vascularization and growth. Thus, type I IFNs appear to be the part of the natural tumor surveillance mechanism. Here we provide an up to date review of how type I IFNs influence the pro- and anti-tumor properties of neutrophils. Understanding these mechanisms is particularly important from a therapeutic point of view.